Pathological manifestations and structural restoration of the Estacio Coimbra bridge (Derby bridge in Recife) (Research, Society and Development, 2022)
The first concrete bridges were built in the 20th century, being widely used in the daily life of the population, with the purpose of locomotion of people, cars and among others. For these structures to be of good use, there must be an extensive study and a good design of the place where this construction will be carried out, and always carry out periodic maintenance of the structure, thus avoiding inconvenience to its users. The objective of this work was to analyze the pathological manifestations present in bridges, having as a research reference the Estacio Coimbra bridge (Ponte do Derby), located in the city of Recife. The results were obtained through the records of the place and some pathological manifestations were observed such as corrosion of the reinforcement, disaggregation of the concrete, efflorescence and cracks, several reasons caused the wear of the structure, for example, the lack of maintenance. Occurring in these failures, it becomes unsafe for users. Therefore, the structure was quite damaged, due to lack of maintenance, which resulted in the pathological manifestations presented in this article, in which corrective maintenance was necessary.